Telocytes in female reproductive system (human and animal). Issue 6 (5th April 2016) - Aleksandrovych, Veronika; Walocha, Jerzy A.; Gil, Krzysztof
Abstract: Telocytes (TCs) are a newly discovered type of cell with numerous functions. They have been found in a large variety of organs: heart (endo‐, myo‐, epi‐ and pericardium, myocardial sleeves, heart valves); digestive tract and annex glands (oesophagus, stomach, duodenum, jejunum, liver, gallbladder, salivary gland, exocrine pancreas); respiratory system (trachea and lungs); urinary system (kidney, renal pelvis, ureters, bladder, urethra); female reproductive system (uterus, Fallopian tube, placenta, mammary gland); vasculature (blood vessels, thoracic duct); serous membranes (mesentery and pleura); and other organs (skeletal muscle, meninges and choroid plexus, neuromuscular spindles, fascia lata, skin, eye, prostate, bone marrow). Likewise, TCs are widely distributed in vertebrates (fish, reptiles, birds, mammals, including human). This review summarizes particular features of TCs in the female reproductive system, emphasizing their involvement in physiological and pathophysiological processes.